LIFE-THREATENING MANIFEST OF LONG-QT-SYNDROME - M. E. Polyak; D. G. Podolyak; O. V. Glazova; E. A. Artyukhina; M. A. Nechaenko; E. V. Zaklyazminskaya (Российский кардиологический журнал, 2014)
Aim. To complete DNA-diagnostics for the patients with syncopes and not showing clinically significant rhythm disorders, but with family anamnesis of sudden death. Material and methods. Clinical case. The patient 22 y.o. consulted at RSCS n.a.Petrovsky with the primary diagnosis of "inherited epilepsy" and complaints on presyncopes and dizziness. During examination there was no data found to prove the inherited epilepsy and clinically significant rhythm disorders. Taking into account the family anamnesis of sudden death a dignosis of "idiopathic ventricular tachycardia" was suggested and the patient underwent two-chamber rate-adaptive cardioverter-defibrillator Maximo II DR D284DRG implantation. DNA-testing revealed a mutation of p.R583H in the gene KCNQ1, that had been previously described as probable to cause type 1 long-QT-syndrome. During the next 12 month after implantation there were 2 proven strobes recorded. The patient was consulted by cardiologist to prescribe beta-blocker therapy.Results. Although there were no clinically significant heart rhythm disorders found, the patient with suspected family type of idiopathic ventricular tachicardia underwent cardioverter-defibrillator setting up procedure. Molecular-genetic methods helped to prove the diagnosis of "long-QT-syndrome type 1" and the cascade family screening was started to choose a treatment strategy for asymptopathic mutation bearers. Conclusion. By the example of the clinical case described we showed a significance of DNA-diagnostics in the diagnosis clarification, treatment strategy choice and sufficient medical-genetic consulting for the disease mentioned.